2015
DOI: 10.1016/j.ascom.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Data compression in the petascale astronomy era: A GERLUMPH case study

Abstract: As the volume of data grows, astronomers are increasingly faced with choices on what data to keep -and what to throw away. Recent work evaluating the JPEG2000 (ISO/IEC 15444) standards as a future data format standard in astronomy has shown promising results on observational data. However, there is still a need to evaluate its potential on other type of astronomical data, such as from numerical simulations. GERLUMPH (the GPU-Enabled High Resolution cosmological MicroLensing parameter survey) represents an exam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…where size o is size of the original file and size c the size of the compressed file. Recent investigations of lossy JPEG2000 compression for astronomical images (Peters & Kitaeff, 2014;Kitaeff et al, 2015;Vohl et al, 2015) show that it can lend high factors of compression while preserving scientifically important information in the data. For example, Peters & Kitaeff (2014) compressed synthetic radio astronomy data at several levels of compression, and evaluated how the loss affects the process of source finding.…”
Section: Jpeg2000 and Lossy Data Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…where size o is size of the original file and size c the size of the compressed file. Recent investigations of lossy JPEG2000 compression for astronomical images (Peters & Kitaeff, 2014;Kitaeff et al, 2015;Vohl et al, 2015) show that it can lend high factors of compression while preserving scientifically important information in the data. For example, Peters & Kitaeff (2014) compressed synthetic radio astronomy data at several levels of compression, and evaluated how the loss affects the process of source finding.…”
Section: Jpeg2000 and Lossy Data Compressionmentioning
confidence: 99%
“…In the time-critical scenario of DWF, a gain in transmission time offered by data compression is only interesting if compression and decompression can be achieved quickly. To this end, Vohl et al (2015) demonstrated that KERLUMPH 5 -a multi-threaded implementation of the JPEG2000 standard -can compress and decompress large files quickly.…”
Section: Software Design Rationalementioning
confidence: 99%
“…If the development of a theoretical model for the compression is too complex, the most common approach is to estimate the error induced on the results of the data analysis when compressed data are used instead of the original uncompressed ones. For a few examples of the latter approach, see e.g., Vohl et al (2015); Löptien et al (2016).…”
Section: Inputmentioning
confidence: 99%
“…1 . The relation between 2 1 and̃2 1 is defined by relation (2). Orthogonality in defined vector space could be written as condition…”
Section: Karhunen-loève Transformmentioning
confidence: 99%
“…This data is necessary for archiving and distribution among servers and users. Therefore, searching for suitable compression standard is still rather important task [2,3]. There are many compression standards matched to the human visual system (HVS) for multimedia purposes [4].…”
Section: Introductionmentioning
confidence: 99%